The contribution of Ibn al-Baitar in medicine - Kamarudin, Mohd Hider; Shafie, Amir Akramin (IIUM Press, 2011)
The objective of this chapter is to review the contributions of Ibn AI-Baitar on the subject of p1edicine. The importance of this study is intended for the people to appreciate the value of many discoveries and works done by Muslim's scientists during the historical age for instance the exploration of Ibn AI-Baitar on discovering various plants and medicines. The methodology adopted in this chapter is a web based study by searching through several books and articles discussing on ancient Islamic medicine and learn about the contributions of early Muslim's scientists on medicine. The research framework for this chapter is mainly by examine the basic features of Ibn AI-Baitar's works and contributions in the course of medicine and presents it in this chapter